2014
DOI: 10.1105/tpc.114.122903
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone Promotes Degradation of DWARF14, an α/β Hydrolase Essential for Strigolactone Signaling inArabidopsis 

Abstract: Strigolactones (SLs) are phytohormones that play a central role in regulating shoot branching. SL perception and signaling involves the F-box protein MAX2 and the hydrolase DWARF14 (D14), proposed to act as an SL receptor. We used strong loss-offunction alleles of the Arabidopsis thaliana D14 gene to characterize D14 function from early axillary bud development through to lateral shoot outgrowth and demonstrated a role of this gene in the control of flowering time. Our data show that D14 distribution in vivo o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
202
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(224 citation statements)
references
References 94 publications
(187 reference statements)
19
202
3
Order By: Relevance
“…It can be envisioned that once the cell is committed to the branching fate through the activation of SL pathways, the plants want to shut down the branching signals as soon as possible. This could be achieved by destabilization of the receptor D14 upon ligand binding and effector coupling as reported here, followed by ubiquitination-mediated degradation as D14 is subject to proteolysis in cells in the presence of GR24 [22]. While many gaps remain in our understanding of this unusual signaling mechanism, the structural and mutational analyses of the D14/GR24 and D14/GR24/D3 complexes reported in this paper establish the GR24 binding mode in the D14 pocket and identify the D3-binding interface of D14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be envisioned that once the cell is committed to the branching fate through the activation of SL pathways, the plants want to shut down the branching signals as soon as possible. This could be achieved by destabilization of the receptor D14 upon ligand binding and effector coupling as reported here, followed by ubiquitination-mediated degradation as D14 is subject to proteolysis in cells in the presence of GR24 [22]. While many gaps remain in our understanding of this unusual signaling mechanism, the structural and mutational analyses of the D14/GR24 and D14/GR24/D3 complexes reported in this paper establish the GR24 binding mode in the D14 pocket and identify the D3-binding interface of D14.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified the putative transcriptional repressor D53 [19,20] as well as the transcription factor BES1 as SCF D3 substrate targets in response to SL exposure and the D53 paralog SMAX1 in response to karrikin exposure. SLs induce association of D14 with D3/D53 and D3/BES1 complexes and promote SCF D3 -mediated degradation of D53 [19,20], BES1 [21], and D14 itself [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports show that the other known components of SL signaling, D14 and MAX2, are expressed in the same vascularassociated tissues as SMXL7 and are at least partially nuclear (Chevalier et al, 2014;Stirnberg et al, 2007). To explore the colocation of these proteins in more detail, we used both transient expression assays in N. benthamiana and stable expression in Arabidopsis.…”
Section: (E) To (G) Subcellular Localization Of Smxl7-yfp (E) D14-cementioning
confidence: 99%
“…In the second model, SLs are proposed to act throughout the shoot to trigger clathrin-mediated endocytosis of the PIN1 auxin efflux carrier (Crawford et al, 2010;Shinohara et al, 2013). This hinders the establishment of positive feedback-driven, canalized auxin export from buds into the stem, which has been proposed to be required for the outgrowth of buds (Li and Bangerth, 1999;Prusinkiewicz et al, 2009;Crawford et al, 2010;Shinohara et al, 2013 very likely to act as a SL receptor, since it binds and hydrolyses the synthetic SL analog GR24 and is required for sensitivity to SL (Liu et al, 2009;Hamiaux et al, 2012;Waters et al, 2012;Kagiyama et al, 2013;Zhao et al, 2013;Chevalier et al, 2014). D14 acts in concert with the MAX2 F-box protein, which forms part of an SCFtype ubiquitin ligase complex (Stirnberg et al, 2007;Hamiaux et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation